Paleoambiental a partir de Silicobiolitos presentes en Cárcavas de Pampa de Olaén, Córdoba, Argentina - Ayala, R.; Sanabria, J.; Rouzaut, S.; Nuñez, V. (2024)
Fil: Ayala, R. Universidad Nacional de Córdoba; Argentina.